Why verticalize? A study on the verticalization process in cities (Research, Society and Development, 2021)
From the 20th century onwards, substantial morphological changes occurred in the urban space of many cities. These changes were mainly motivated by the idea of modernizing space and by the process known as Baby Boom. Therefore, this research constitutes a bibliographic study about the process of verticalization of cities and aims to discuss and reflect the process of verticalization, evaluating the reasons that lead cities to verticalize and impacts generated by the act of verticalising. Currently, urban centers continue to develop, mainly due to the increase in population and the constant movement of people moving from rural to urban areas. In the case of 21st century Brazilian cities, two characteristics define them: the accelerated pace of densification and urban verticalization. Verticalization is one of the fundamental factors for the modification of urban morphology. It translates as an evolution or modernization of space, but also as a result of economic and political interests. Furthermore, the process of verticalization of the urban landscape is a response to demographic growth and the decrease in space available for housing and for social and economic purposes.